O discurso político da Igreja Universal do Reino de Deus a respeito da esquerda: Um estudo de caso do programa Entrelinhas - Barros, Marcelo Silva de (Numen, 2023)
The purpose of this article is to understand characteristics of the political discourse of the Universal Church of the Kingdom of God (UCKG) regarding the left-wing aired on the Univervideo streaming platform, focusing its investigations on one of its talk shows, entitled Entre Linhas, opened in 2020. It presents how ideological aspects of these discourses are articulated and their possible connections with theological elements that would influence the narratives of the UCKG. The analysis is intended to contribute to the understanding of the UCKG's behavior in the political choices it makes on the national scene, and the time frame extends from the 2020 municipal elections to the 2022 presidential elections.